Determination Of Profitability With Non-Performing Financing As Moderation - Faiz Nasokha; Fetria Eka Yudiana (LPPM ISNJ Bengkalis, 2022)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Third Party Funds (TPF), and Islamicity Performance Index, which includes Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), and Equitable Distribution Ratio (EDR) on profitability with Non-Performing Financing (NPF) as a moderating variable at Islamic commercial banks in Indonesia for the 2015-2020 periods. This type of research is quantitative research using Moderate Regression Analysis (MRA) as data analysis and using secondary data in the form of panel data. The sample used was several banks with a purposive sampling method and processed using the E-Views application tool. The results showed that the Islamicity Performance Index, namely ZPR, partially positively and significantly affects profitability. In contrast, CAR, TPF, NPF, and other Islamicity Performance Index variables, namely PSR, and EDR, do not affect profitability. NPF can moderate the effect of TPF on profitability, while NPF cannot moderate the effect of profitability and the three Islamicity Performance Index variables on profitability. This research is practically to find out the determinant variables that increase profitability and reduce non-performing financing to maximize the profits of Islamic commercial banks.